Analysis of Single Actuator for Rehabilitation Device of Leg Weakness - Samat, Khairul Fadzli; Hussein, Mohamed; M.R., Safizadeh (Trans Tech Publications, 2013)
In this paper, the development of rehabilitation device for patients who encounter walking weakness due to post-stroke effect is presented. The kinematic analysis was carried out in the initial stage of development in order to have an efficient mechanism. As guide to design the device, the walking motion of healthy physical subject for speed of 1 km/h was used and subsequently a mechanism was designed to create similar walking motion. The device functions to inculcate the movement of thigh and calf through appropriate rotation of hip and knee. A single actuator of direct current (DC) motor is used to actuate the rotation of the hip and the knee joints mechanism. The kinematic analysis of constructed device has been performed and the results conformed the functionality of the suggested mechanism. The fabricated prototype proves the combination of DC motor and cam mechanism can actuated the movement of hip and knee joint simultaneously and subsequently reduced the power consumption.